Website Based Digital Assessment Model Jogja Madrasah Digital (JMD) in Learning Evaluation in Madrasah Ibtidaiyah Negeri 1 Yogyakarta - Mardiah, Desni (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: This study aims to identify challenges and opportunities in the Jogja Madrasah Digital (JMD) website as an assessment model in learning evaluation at Madrasah Ibtidiyah Negeri 1 Yogyakarta. Methodology: Using descriptive qualitative research method, data were obtained through interviews, observations and literature studies. Main Findings:The results showed that the Jogja Madrasah Ditigal (JMD) website was efficient enough to be used for assessment in learning evaluation at Madrasah Ibtidaiyah Negeri 1 Yogyakarta, but there were still technical obstacles such as lack of support for essay questions and Arabic fonts and inadequate infrastructure. Therefore, further development of the Jogja Madrasah Digital (JMD) website is needed. Novelty/Originality of this study: This study opens new insights into the importance of integrating learning evaluation using multimedia, so that evaluation is more effective and efficient.